Are sub-elite athletes at higher risk of eating disorders, exercise addiction, depression, and low energy availability compared with elite athletes - Lichtenstein, M. B.; Hertz, S. P. T.; Johansen, K. K.; Rytter, J.; Sundgot-Borgen, J.; Torstveit, M. K.; Holm, L.; Melin, A. K. (Clinical Journal of Sport Medicine, 2024)
Objective The main objective of this study was to investigate the risk of eating disorders, exercise addiction, depression, and low energy availability (LEA) in Danish female and male elite compared with sub-elite athletes.